Relationship Between Mitochondrial Structure and Bioenergetics in Pseudoxanthoma elasticum Dermal Fibroblasts - Lofaro, Francesco Demetrio; Boraldi, Federica; Garcia-Fernandez, Maria; Estrella, Lara; Valdivielso, Pedro; Quaglino, Daniela (Frontiers in Cell and Developmental Biology, 2020)
Pseudoxanthoma elasticum (PXE) is a genetic disease considered as a paradigm of ectopic mineralization disorders, being characterized by multisystem clinical manifestations due to progressive calcification of skin, eyes, and the cardiovascular system, resembling an age-related phenotype. Although fibroblasts do not express the pathogenic ABCC6 gene, nevertheless these cells are still under investigation because they regulate connective tissue homeostasis, generating the “arena” where cells and extracellular matrix components can promote pathologic calcification and where activation of pro-osteogenic factors can be associated to pathways involving mitochondrial metabolism. The aim of the present study was to integrate structural and bioenergenetic features to deeply investigate mitochondria from control and from PXE fibroblasts cultured in standard conditions and to explore the role of mitochondria in the development of the PXE fibroblasts’ pathologic phenotype. Proteomic, biochemical, and morphological data provide new evidence that in basal culture conditions (1) the protein profile of PXE mitochondria reveals a number of differentially expressed proteins, suggesting changes in redox balance, oxidative phosphorylation, and calcium homeostasis in addition to modified structure and organization, (2) measure of oxygen consumption indicates that the PXE mitochondria have a low ability to cope with a sudden increased need for ATP via oxidative phosphorylation, (3) mitochondrial membranes are highly polarized in PXE fibroblasts, and this condition contributes to increased reactive oxygen species levels, (4) ultrastructural alterations in PXE mitochondria are associated with functional changes, and (5) PXE fibroblasts exhibit a more abundant, branched, and interconnected mitochondrial network compared to control cells, indicating that fusion prevail over fission events. In summary, the present study demonstrates that mitochondria are modified in PXE fibroblasts. Since mitochondria are key players in the development of the aging process, fibroblasts cultured from aged individuals or aged in vitro are more prone to calcify, and in PXE, calcified tissues remind features of premature aging syndromes; it can be hypothesized that mitochondria represent a common link contributing to the development of ectopic calcification in aging and in diseases. Therefore, ameliorating mitochondrial functions and cell metabolism could open new strategies to positively regulate a number of signaling pathways associated to pathologic calcification.